Grazing effects on mountain rangeland diversity in north-eastern Tunisia - Jaouadi W.; Mechergui K.; Khouja M.L. (Ecosystem services and socio-economic benefits of Mediterranean grasslands, 2016)
Although the effects of controlled grazing, heavy grazing and no grazing on vegetation structure have been extensively studied in a wide range of ecosystems, the effects of grazing on mountain lands are still largely unknown in Tunisia. Two areas traditionally grazed by sheep and goats in northeastern Tunisia (continuously grazed and controlled grazing) and an ungrazed area were sampled to evaluate the effects of grazing intensity on mountain rangelands. We examined the respective effects of heavy grazing, controlled grazing and no grazing on total vegetation cover, species richness and the Shannon-Wiener diversity index. Sampling was done from 2009 using permanent transects under different grazing intensities. Results show that vegetation dynamics in mountain rangelands respond strongly to changes in grazing management. The controlled grazing impact maintains resilient rangelands and ensures a sustainable flow of rangeland goods and services to livestock. The resting periods in the controlled grazing allow plants to recover before they are grazed again. The vegetation cover, species richness, Shannon-Wiener diversity index and species composition were significantly greater on the un-grazed site and significantly lower on the heavily grazed site.
15. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM International Network for the Research and Development of Pastures and Fodder Crops, 2016/04/12-14, Orestiada (Greece)